The Effect of the EMDR Flash Group Technique on Test Anxiety, Traumatic Stress, and Coping Mechanisms in Students Taking a Gap Year - Kubilay, D.; Yasar, A. B.; Citil, C.; Ugur, B.; Kutuk, S.; Sevil, I. G.; Bedel, G. (Cambridge Univ Press, 2025)
[Abstract Not Available]
Keywords: [Keyword Not Available]